The analysis of conversion words in HSK Level 1 vocabulary list - Cheng, Ching Yee (2017)
There are certain inquiries that still can be open to discussion in the issue of categorizing the part of speech of conversion words in the HSK Level 1 Vocabulary List (Version 2015). Without a clear specification of the part of speech, it will be difficult for Chinese beginner learners in learning conversion words. Thus those learners will face difficulties in taking the HSK Level 1 exam. Therefore this paper aims to review the conversion words in the HSK Level 1 Vocabulary List (Version 2009) and (Version 2015). Those conversion words will be compared with 26 sets of HSK Level 1 papers by using qualitative analysis. The result showed that some of the conversion words are over-categorized or under-categorized. This paper states some suggestions to improve the issue of the part of speech’s categorization for conversion words in HSK Level 1 Vocabulary List based on the qualitative description of the result. These suggestions hope to increase the efficiency to teach and learn the conversion words for both teachers and learners.